Changing Trends in Uropathogen Distribution and Antibiotic Resistance Patterns in Nairobi, Kenya: A Longitudinal Study - Darren Smith; Aysah Jalal (Sriwijaya Journal of Internal Medicine, 2023)
Introduction: Urinary tract infections (UTIs) remain a significant global health challenge, exacerbated by the increasing prevalence of antibiotic resistance. This study aimed to investigate the changing trends in uropathogen distribution and antibiotic resistance patterns in Nairobi, Kenya, over a five-year period. Methods: A retrospective longitudinal study was conducted using laboratory records from three major hospitals in Nairobi. Data on uropathogens isolated from urine cultures and their antibiotic susceptibility profiles were collected from January 2018 to December 2023. Descriptive statistics, chi-square tests, and logistic regression analysis were used to analyze the data. Results: A total of 12,475 urine cultures were analyzed. Escherichia coli was the most prevalent uropathogen (48.2%), followed by Klebsiella pneumoniae (18.6%), Staphylococcus saprophyticus (12.5%), Proteus mirabilis (8.7%), and Enterococcus faecalis (7.1%). A significant increase in the prevalence of K. pneumoniae (p<0.001) and a decrease in E. coli (p=0.023) were observed over the study period. Resistance rates to commonly used antibiotics, including ampicillin, trimethoprim-sulfamethoxazole, and ciprofloxacin, increased significantly for most uropathogens. Multidrug resistance was observed in 32.1% of isolates, with a significant increase over time (p<0.001). Conclusions: This study highlights the dynamic nature of uropathogen distribution and antibiotic resistance patterns in Nairobi. The increasing prevalence of K. pneumoniae and the rise of multidrug resistance pose a serious threat to public health. Conclusion: surveillance and the implementation of antimicrobial stewardship programs are crucial to guide empirical treatment and preserve the effectiveness of available antibiotics.